Navigating Educational Quality in the New Normal: Strategic Adaptation through a Five-Stage Internal Audit Framework for Higher Education Resilience - Eko Nurhaji Purnomo; Abdur Rofik; suwadji (Universitas Islam Raden Rahmat Malang, 2025)
The post-pandemic